2017
DOI: 10.17707/agricultforest.63.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of attitudes of honey consumers in the municipality of Novi Grad (Bosnia and Herzegovina)

Abstract: Beekeeping is one of the important branches of animal husbandry, and it is also important in the municipality of Novi Grad in Bosnia and Herzegovina (BaH). Honey producers should be interested in what consumers think of honey and which factors are crucial for their commitment to purchase honey. Therefore, there has been a study of honey consumer attitudes conducted by a survey of 100 randomly selected consumers. The subject of the survey was to determine the consumers' attitudes regarding the amount of honey t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Niyaz and Demirbaş (2017) found that 34% of consumers always consumed honey, while the majority of the consumers never consumed other bee products. Klickovic et al (2017) found that 47% of consumers consume honey several times a week. On the other hand, the percentage of respondents who consume honey very rarely is 12%.…”
Section: Resultsmentioning
confidence: 99%
“…Niyaz and Demirbaş (2017) found that 34% of consumers always consumed honey, while the majority of the consumers never consumed other bee products. Klickovic et al (2017) found that 47% of consumers consume honey several times a week. On the other hand, the percentage of respondents who consume honey very rarely is 12%.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 51.2% of consumers buy honey from beekeepers whom they generally know, and 41% of consumers buy honey from market and bazaar. Klickovic et al (2017) found that 47% of consumers consume honey several times a week. On the other hand, the percentage of respondents who consume honey very rarely is 12%.…”
Section: Main Findings Regarding Honey Consumption Consciousness Of C...mentioning
confidence: 99%
“…Regarding the variety of honey consumers in Croatia (Brščić et al, 2017), Romania (Pocol & Bolboacă, 2013), the USA (Unnevehr & Gouzou, 1998), the Republic of Congo (Gyau et al, 2014), and Saudi Arabia (Zulail et al, 2014) prefer mostly mono‐floral rather than multifloral honey. Price remains one of the most important attributes that affect the purchase of honey in Italy (Cosmina et al, 2016), Hungary (Ványi et al, 2011), Poland (Kowalczuk et al, 2017; Roman et al, 2013a), Romania (Pocol & Bolboacă, 2013), Bosnia and Herzegovina (Kličković et al, 2017), and the Asian countries (Yeow et al, 2013). Simultaneously, preferences for other extrinsic characteristics of honey, linked to brand and reputation, have been reported to affect the purchase of honey in Australia (Batt & Liu, 2012), Denmark (Jensen & Mørkbak, 2013), the USA (Wu et al, 2015), and the Asian countries (Yeow et al, 2013) as well.…”
Section: Introductionmentioning
confidence: 99%